Media optimization for the production of thermostable and organic solvent tolerant lipase by solid state fermentation from palm kernel cake - Zubairi, Hidayah; Alam, Md. Zahangir; Salleh, Md. Noor; Salleh, Hamzah Mohd. (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Lipases are important hydrolytic enzymes that catalyze hydrolysis of the triglycerides, esterification and transesterification reactions. These enzymes are of great interest for many reasons include they do not require cofactors, remain active in organic solvent, used with broad range of substrates and exhibit high enatino- and regio- selectivity (Rahman et al., 2005). Very few lipases have been reported having both characteristics such as thermostable and organic solvent-tolerant suitable in fermentation of solid wastes for industrial processes (Masomiama, 2013). Production of thermostable and organic solvent tolerant lipase in solid state fermentation (SSF) using Bacillus smitthi strain PKC-P1 isolated from Palm Kernel Cake (PKC) has been investigated in this study. This strain with 11.13 U/g of lipase activity was optimized by statistical approach. The increment of lipase activity to 46.6 U/g was observed in One-factor-at-a-time (OFAT) studies at 65 o C, pH 10.0, olive oil (1.25%), yeast extract (2.0%), peptone (2.0%) and inoculum size (6%). A successful improvement of lipase production was achieved at the end of this study. This finding revealed and proving that bacterial locally isolated from oil-rich environment has potential as a source of more economical enzyme for biotechnological application.